2019
DOI: 10.1136/bmjopen-2018-028706
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical enhanced recovery after surgery (ERAS) programme for elective craniotomies: are patients satisfied with their experiences? A quantitative and qualitative analysis

Abstract: ObjectiveTo evaluate patient satisfaction and associated predictors at discharge, as well as patient experience at 30-day follow-up, in a neurosurgical enhanced recovery after surgery (ERAS) programme.DesignA single-centre, prospective, randomised controlled study.SettingA tertiary hospital in China.ParticipantsA total of 140 neurosurgical patients aged 18–65 years old who had a single intracranial lesion and were admitted for elective craniotomy between October 2016 and July 2017 were included.InterventionsPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 18 publications
(42 reference statements)
0
41
0
2
Order By: Relevance
“…Recently we have implemented a novel multidisciplinary, evidence-based, neurosurgical ERAS program for elective craniotomy patients in a single center 1 . And evidences have suggested that the ERAS protocol could reduce the length of hospital stay postoperatively and that in turn enhanced the patients' recovery 29 , 30 . In this study, we still based on the same protocol, but with focusing on the postoperative pain control, which are vital component to the whole picture of current neurosurgical ERAS protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Recently we have implemented a novel multidisciplinary, evidence-based, neurosurgical ERAS program for elective craniotomy patients in a single center 1 . And evidences have suggested that the ERAS protocol could reduce the length of hospital stay postoperatively and that in turn enhanced the patients' recovery 29 , 30 . In this study, we still based on the same protocol, but with focusing on the postoperative pain control, which are vital component to the whole picture of current neurosurgical ERAS protocol.…”
Section: Discussionmentioning
confidence: 99%
“…laminectomy and discectomy, especially within Enhanced Recovery After Surgery (ERAS) protocols. [8][9][10][11][12] Both general anesthesia (GA) and SA have been adopted for surgical treatment of lumbar spine disorders, but GA is used far more widely, and exclusively, in many settings. Regional anesthesia is frequently used in orthopedic surgery and as part of ERAS protocols in other specialties.…”
mentioning
confidence: 99%
“…Wang et al presented the first published evidence for ERAS in craniotomy in 2019, with 140 patients undergoing surgery for both supra and infratentorial tumors [ 15 ]. In a series of closely spaced publications (same trial number), this group reported improved benefits in glucose homeostasis, [ 16 ] patient satisfaction [ 17 ], and decreased postoperative nausea and vomiting (PONV) [ 18 ], one retracted since [ 19 ]. To the best of our knowledge, at the time of submission, we are the first group from outside of China to report the implementation and benefits of ERAS protocol in craniotomy patients.…”
Section: Discussionmentioning
confidence: 99%